Cervicobrachial compression syndromes - Valls, Alberto (Cirugía del Uruguay, 1972)
Four patients, who underwent fíve operations, lead the author to consider the problem of cervico-brachial compression syndromes. Their symptomatology -neurological and vascular, mainly of the spasmodic type and connected with certain attitudes of the upper limb- is related with an upset in the harmony between the cervico-thoracic skeleton and the scapular girdle, in which case the action of the scalenus, of a cervical rib or fírst dorsal rib, oftentimes abnormal, is felt. Surgical treatment is through cervical approach, though lately high intra-tporacic approaches have been atte:npted, with resection of the scalenus anterior and fi.brotic formations compressing the passage, as well as the cervical rib when necessary. In the latter case this has been facilitated by the prior section of the scalenus anterior and fibrotic formations described by Sebileau. The pleural dome consequently descends. Results obtained have been satisfactory and the operation for anybody with the necessary anatomical knowledge, is a simple one.